Timeout-Based Information Forwarding Protocol for Wireless Sensor Networks. (2007) - Jeong Jeong, Wootae Wootae; Nof Nof, Shimon Y. Shimon Y.
Abstract : Recent wireless microsensor network protocols provide more flexible leverage to the applications with dynamically changing topology, but they should be designed to overcome energy constraints, the bandwidth limit, and system latency. Thus, microsensor network protocols should be effective both in energy and in latency. In addition, they should be evaluated through designated tools at each level of networking characteristics. This paper proposes a new Timeout-based Information Forwarding (TIF) protocol for wireless sensor networks. It uses a relatively simple logic to forward the data packet with multi-hop fashion to reduce the overall network energy consumption. The TIF protocol has been implemented into a network evaluation tool, called TIE/MEMS, and provides a design strategy for distributed wireless sensor network systems needed for various emerging applications. The simulated results show that the TIF protocol has low energy consumption and provides design guidelines between energy consumption and latency according to the number of hops by adjusting weight values in the timeout function.